Fourth Five Year Plan of Assam A Draft Outline - Planning Commission (Planning Commission, 1968)
Assam is a land-locked State surrounded by the foreign territories of Burma and East Pakistan. It is situated very near to Tibet and China proper and has a common border with West Bengal, Nagaland, Tripura and Manipur. Geographically and from the point of view of communications with the rest of the country, Assam forms the core of the entire north-eastern part of the country comprising of Assam, Nagaland, North East Frontier Agency, Manipur and Tripura. All lines of communication to these areas pass through Assam. By virtue of its geographical position, Assam occupies a very important position in the political and physico-geographical map of the country.
Government of Assam, Planning and Development Department